The Splenic Artery and Segmental Branches Morphometric Study in Humanoid Cadaver Spleens by Method of Dissection - Motasim Billah, Nadia Majeed, Samah Fatima Qasarani, Namra Asif, Aqsa Mazhar, Asma Ashraf (Pakistan Journal of Medical & Health Sciences, 2022)
In the human body; the major lymphatic organ is the spleen supplied by the splenic artery, the main division of the celiac trunk. It crosses the lienorenal ligament and approaches the spleen hilum where it splits into 2-3 main branches, each of which divides mainly into 2-4 secondary branches. Also, inferior and superior polar arteries arise from the primary branches or splenic trunk and pass into the spleen pole without entrance in the hilum. The purpose of this analysis was to understand the segmental branches morphometry of the polar and splenic arteries. Methods: The analysis was performed on 86 spleens collected from adult human cadavers of not known gender, stored in formalin 10% solution obtained from the Anatomy and Forensic Medicine Department, by dissection. Place and Duration: In the department of anatomy, Multan Medical and Dental College and Bacha Khan Medical Complex Swabi for six months duration, from August 2021 to January 2022. Results: In 59 (68.6%) spleen samples; there were 2 primary branches, 23 (26.7%) samples have three primary branches, and 4 (4.7%) specimens have four primary branches. 20 (23.3%) samples have superior polar arteries, 34 (39.5%) have inferior polar arteries, and both inferior and superior polar arteries in 7 (8.1%) samples. The superior polar artery length varies from 0.8-5.51 cm, with 2.80 cm of average length and 2.4 cm median length. The inferior polar artery length ranged from 0.9-5.90 cm, with 3.17 cm of average length and 3.30 cm median length. The superior PB diameter ranged from 0.8-4.12 mm, with 2.20 mm average length and 2.4 mm median length. The mean diameter of middle PB ranged from 0.8 mm to 3.6 mm, with an average of 2.10 mm and 2.4 mm median length. The PB inferior diameter ranged from 0.6 mm to 4.4 mm, with an average of 2.13 mm and 2.10 mm median length. The superior polar artery diameter ranged from 0.5-3.1 mm, with 1.40 mm average length and 1.4 mm of median. The inferior polar artery diameter varies from 0.5-2.9 mm, with 1.3 mm of an average diameter with 1.4 mm median. Conclusions: As various splenic sparing surgeries depend on better information of the vascular anatomy of the spleen, this analysis enhances the current information about the segmental branches’ morphometry of the splenic artery. Keywords: Splenic artery, Polar artery and Segmental branches